INFLUENCE OF F CONTENT ON THE COMPOSITION OF AL-RICH SYNTHETIC PHLOGOPITE: PART I. NEW INFORMATION ON STRUCTURE AND PHASE-FORMATION FROM 29SI, 1H, AND 19F MAS NMR SPECTROSCOPIES - Fechtelkord M.; Behrens H.; Holtz F.; Fyfe C.A. (My University, 2003)
The influence of F content on the formation and stability of Al-rich phlogopite has been investigated. Samples with varying OH/F-ratios and nominal gel compositions of K(Mg3-xAlx)(Al1+xSi3-xO1O)(OH)y (F)2-Y (0-0 less than or qequal to X less than or equal to 0.8 and 0.5 less than or equal to y less than or equal to 1.8) were studied using 29Si, 1He and 'IF MAS NMR spectroscopies, powder X-ray diffraction, electron-probe microanalysis, and scanning electron microscopy. The synthetic phlogopites were synthesized from sol-gels in cold-seal pressure vessels at 1073 K, 2 kbar. The main phase (phlogopite) and three other impurity phases [corundum ((alpha-Al2O3), kalsilite (KA1Si04), and potassium aluminum hexafluoride (K3AlF6'0-5H20)] were clearly identified by powder X-ray diffraction and electron-probe microanalysis. For phlogopite, the unit-cell parameters a0 and b0 decrease whereas co increases with increasing Al-content (x). The average crystal size of phlogopite is about 1-2 epsilonm. The 21Si MAS NMR spectra show up to four resonances at approximately -91, -87, -83, and -80 ppm, which can be assigned as Q3(n At) signals with n = 03. The ideal Si/IVAl ratio calculated from the initial composition is always lower than that derived experimentally. Hydroxyl-rich compositions indicate an increased At-content in the tetrahedral sheets, suggesting a stabilizing effect on the formation of At-rich phlogopite. These conclusions are supported by 1H and 'IF MAS NMR spectra. The 1H MAS NMR spectra show a water signal at 4.7 ppm, a signal due to M92AIOH at 1.8 ppm, and a signal due to M930H at 0.7 ppm. The 'IF MAS NMR spectra exhibit a signal for M92AIF at -150 ppm, one due to AIF6 (K3AIF6.0.5H20) at -157 ppm, and one for M93F at -174 ppm. Comparison of the'H and 19F MAS NMR spectra for different A1- and F-contents reveals a non-statistical distribution of F- and OH-groups at the crystallographic sites in the octahedral sheets where F prefers sites coordinated by three Mg, and OH sites with At in the nextnearest coordination sphere.
Keywords: MINERALOGY